European Union: Pesc looking for consistency in the Central African Republic - (:unkn) unknown (My University, 2014)
Whether in the context of the ESDP or today of the CSDP, the implementation of the Pesc operational instrument is laborious. The Franco-British team bends under the influence of NATO and the hesitations of Germany devote the blockage of a military action of the EU. Since 2003, however, European policy has been growing in sub-Saharan Africa. Under the Eufor (European Union Force) label, France is conducting operational actions, gradually giving consistency and visibility to La Pesc.
Keywords: African Research